Search Behavior of Individual Foragers Involves Neurotransmitter Systems Characteristic for Social Scouting - Chatterjee, Arumoy; Bais, Deepika; Brockmann, Axel; Ramesh, Divya (Frontiers in Insect Science, 2021)
Behavioral specialization in honey bees is regulated by hormones and neuromodulators that tune neuronal activity and gene expression, and can be viewed as a temporarily fixed behavioral state associated with a specific brain state. Honey bee scouts, which search for new food sources, show a higher expression of genes involved in glutamate, GABA and catecholamine signaling than recruits that remain loyal to a food source. We asked whether recruits visiting a feeder initiated a search behavior when the feeder was experimentally removed, and if similar neuromodulators might be involved in the initiation and performance of that behavior. We found that recruits perform a relatively stereotyped search behavior that shows inter-individual variation in its intensity. Quantitative single brain mass spectrometric analyses showed that glutamate and GABA titers changed during search behavior supporting the hypothesis that behavioral specialization in social insects is based on reinforcing brain molecular processes involved in solitary behavior.